The Influence of Interactive Media Flashcards on the Process of Memorizing the Qur'an in Early Childhood - Liana; Trisya Sumiati; Yohanes Bahari; Warneri (CV. Creative Tugu Pena, 2024)
This research aims to examine the effect of using interactive media in the form of